Control of myopia using orthokeratology lenses in Scandinavian children aged 6 to 12 years. Eighteen‐month data from the Danish Randomized Study: Clinical study Of Near‐sightedness; TReatment with Orthokeratology Lenses (CONTROL study). Issue 2 (7th July 2021) - Jakobsen, Trine Moldrup; Møller, Flemming
Abstract: Purpose: To investigate the efficacy of myopia control defined by axial elongation and safety of orthokeratology lenses (OKL) in a Scandinavian (Danish) population. Methods: Sixty Danish children aged 6–12 years with myopia ranging from 0.5 to 4.75 dioptres (D) spherical component and refractive astigmatism ≤2.5 D in both eyes were randomly assigned to either OKL or single‐vision spectacles (SVS). Study duration was 18 months. Outcome measures were axial length (AL) measured with Lenstar LS900 (Haag‐Streit, Koeniz, Switzerland) and adverse events graded with Efron Grading Scale for Contact Lens Complications. Results: Nineteen participants completed the 18‐month follow‐up in the OKL group and 28 in the SVS group. The average AL elongation in the OKL group was 0.24 mm smaller as compared to the SVS group (95% confidence interval 0.12–0.36, mixed model adjusted for baseline sex, age and AL). There were no fast progressors (>0.75 D/year) in the OKL group during the follow‐up period in contrast to 22% in the SVS group. No treatment‐requiring or vision‐threatening adverse events were observed. Conclusion: Orthokeratology lenses reduced AL elongation in myopic Scandinavian children by 59%, with no treatment‐requiring or vision‐threatening adverse events. The results align with outcomes of previous clinical trials.